Polycyclic aromatic hydrocarbons (PAHs) in the settled dust of automobile workshops, health and carcinogenic risk evaluation - Ali, Nadeem; Ismail, Iqbal Mohammad Ibrahim; Khoder, Mamdouh; Shamy, Magdy; Alghamdi, Mansour; Al Khalaf, Abdulrahman; Costa, Max (The Science of the total environment, 2017)
There are studies available on the occurrence of PAHs in indoor settled dust from residential and different occupational settings in literature but limited data is available on their occurrence and potential health risk assessment in automobile workshops. In recent decades Saudi Arabia has experienced tremendous growth in the petroleum industry and as a result, the automobile industry is booming. People working in automobile workshops are at a greater risk of exposure to chemicals releasing from the petroleum products. The main objective of this study was to report PAHs in settled dust from different automobile workshops of Jeddah, Saudi Arabia, and evaluate health risk for workers through dust exposure. Pyrene (1585–13500ng/g), Benz[a]anthracene (<LOQ–5065ng/g), and Phenanthrene (280–4860ng/g) were the major PAHs and ∑12PAHs concentrations ranged between 7620 and 30800ng/g. Profile of PAHs was different in dust from small and heavy vehicle workshops. For workers, health risk assessment was calculated based on benzo[a]pyrene equivalent carcinogenic power (BaPE), incremental lifetime cancer risk (ILCR), and daily exposure to PAHs via dust ingestion. The median concentration of BaPE was 285ng/g, ILCR was up to 6.78×10−3 (exceeded reference values of USEPA (range between 1×10−6 and 1×10−4)), and worker's exposure via dust ingestion on daily bases reached up to 33ng/kgbw/day for ∑12PAHs. This study showed people working in automobile workshops in the studied area are getting expose to high levels of PAHs via dust ingestion, inhalation, and dermal contact. This is the first study reporting PAHs in automobile workshops settings from Middle East. The incremental lifetime cancer risk to workers via dust exposure exceeded set limits of USEPA. [Display omitted] •First report on the occurrence of PAHs in dust from automobile workshops of KSA•∑12PAHs were higher in dust from small vehicle than heavy automobile workshops.•Pyrene was the major PAHs in dust from both small and heavy vehicle workshops.•Incremental lifetime cancer risk estimated values were higher than USEPA set limits.•Exposure to carcinogenic PAHs via dust is high for workers in small vehicle workshop.